Risk factors, prevalence, and course of severe fatigue after breast cancer treatment: a meta-analysis involving 12 327 breast cancer survivors. (2nd March 2016) - Abrahams, H. J. G.; Gielissen, M. F. M.; Schmits, I. C.; Verhagen, C. A. H. H. V. M.; Rovers, M. M.; Knoop, H.
Abstract : This first meta-analysis on fatigue in breast cancer survivors showed that about one in four survivors suffers from severe fatigue. Risk factors of severe fatigue were higher disease stages, chemotherapy and a combination of surgery, radiotherapy, and chemotherapy, both with and without hormone therapy. Having a partner, receiving only surgery, and surgery plus radiotherapy decreased the risk. Abstract: Background: This meta-analysis aimed to (i) examine demographic, disease-related, and treatment-related risk factors, (ii) estimate the prevalence, and (iii) describe the course of severe fatigue following breast cancer (BC) treatment. Methods: PubMed, PsycINFO, Cochrane, CINAHL, and Web of Science were systematically searched from inception up to 23 November 2015. Risk factors and prevalence rates were analyzed with inverse variance random-effects analyses. Heterogeneity was studied with sensitivity analyses. Results: Twenty-seven studies were included ( N = 12 327). Breast cancer survivors (BCS) with a partner were at lower risk for severe fatigue than survivors without a partner [risk ratio (RR) 0.96, 95% confidence interval (CI) 0.93–0.98]. Survivors with stage II or III cancer, and survivors treated with chemotherapy were at higher risk for severe fatigue than survivors with stage 0 or I cancer and without chemotherapy (RR respectively 1.18, 95% CI 1.08–1.28; 1.12, 95% CI 1.06–1.19). Survivors treated with surgery, radiotherapy, and chemotherapy, and survivors with this combination plus hormone therapy were at higher risk than survivors with other treatment combinations (RR respectively 1.18, 95% CI 1.05–1.33; 1.38, 95% CI 1.15–1.66). Survivors treated with surgery and surgery plus radiotherapy were at lower risk than survivors with additional treatments (RR respectively 0.83, 95% CI 0.70–0.98; 0.87, 95% CI 0.78–0.96). Hormone and targeted therapy were no significant risk factors. The pooled prevalence of severe fatigue was 26.9% (95% CI 23.2–31.0), but this should be interpreted with caution because of high heterogeneity. A relatively large decrease in the prevalence of severe fatigue seemed to occur in the first half year after treatment completion. Conclusions: Approximately one in four BCS suffer from severe fatigue. Risk factors of severe fatigue were higher disease stages, chemotherapy and receiving the combination of surgery, radiotherapy, and chemotherapy, both with and without hormone therapy. Having a partner, receiving only surgery, and surgery plus radiotherapy decreased the risk.